Photoelastic Refractive Index Changes in GaAs Investigated by Finite Element Method (FEM) Simulations - Daniel T. Cassidy (Optics)
Changes in the refractive indices of a GaAs laser chip owing to bonding strain are investigated by two-dimensional (2D) and three-dimensional (3D) finite element method (FEM) simulations. The strain induced by die attach (i.e., the bonding strain) was estimated by fitting simulations to the measured degree of polarisation (DOP) of photoluminescence from the facet of the bonded chip. Changes in the refractive indices were estimated using the strains obtained from fits to DOP data. Differences between the 2D and 3D FEM estimations of the deformation and of the photo-elastic effect are noted. It is recommended that 2D FEM simulations be used as starting points for 3D FEM simulations. Elastic constants for GaAs in plane-of-the-facet coordinate systems for 2D (plane stress and plane strain) and 3D FEM simulations are given.